Removal of Chemical Oxygen Demand, Colorants and Non-Biodegradable from Leachate Using KMnO4 - Tran, Le Minh; Vu, Kiem Thuy (JST: Engineering And Technology For Sustainable Development, 2024)
Leachate is known to have complicated compositions nd hard to be treated effectively. However, the results presented in this paper show that large proportions of COD, colorants and some non-biodegradable groups could be reduced significantly at the preliminary stage of oxidation process using a strong oxidizing agent such as potassium permanganate (KMnO4). At the initial pH of 7.5, the concentrations of 10,800mg/L COD, 5,926 color (Pt-Co), 133-1,034 ppb polycyclic aromatic hydrocarbon (PAH), 7.49 – 712 ppb organochlorine compounds (OCS) and 21.54 – 2,560 ppb organophosphorous compounds (OPS) were investigated. Within 2 hours of treatment with the initial KMnO4 concentration of approximate 1 g/L and air flow rate of 5 L/minute, the removals of COD, color, groups of PAH, OCS and OPS from leachate were found to be 57%, 93% and over 90%, respectively. These results show that this oxidation process is more effective compared to the coagulation processes with iron or aluminum salts and this technique can be a help to improve the leachate treatment efficiency.